Consumer perceptions of CSR: (how) is China different?. Issue 5 (14th September 2015) - Kolk, Ans; Dolen, Willemijn van; Ma, Leiming
Abstract : Purpose: – Most studies on consumers and corporate social responsibility (CSR) have focused on Western contexts. Consequently, good insight is lacking into non-Western markets where consumers may respond differently. China is a case in point, despite the popularity of the CSR concept and high societal expectations of firms. The purpose of this paper is to examine how Chinese consumers perceive the underlying components of CSR found in Western countries; whether their CSR expectations differ for local Chinese compared to foreign firms; and whether results differ across regions within China. Design/methodology/approach: – A country-wide study was done using a questionnaire to collect data in seven distinctive regional markets across China. Findings: – Findings show that the originally Western CSR construct seems generalizable to China, but consumers across all regions perceive two rather than four components: one combining economic and legal responsibilities (labelled "required CSR") and another combining ethical and philanthropic responsibilities ("expected CSR"). Consumers expect local Chinese firms to take more responsibility than foreign firms, particularly for required CSR. Research limitations/implications: – This study focused on consumer perceptions, not on actual buying behaviour, which is a potential area for further research. Follow-up investigation to see whether the findings regarding the CSR concept also hold in other emerging and developing countries would be worthwhile. This also applies to an extension of the different expectations vis-à-vis foreign and local firms. Practical implications: – The study gives more insight into notions of standardization and adaptation with regard to CSR, considering China compared to other countries and China's different internal markets. This is relevant for international marketers confronted with (potential) investments and activities in China, inbound or outbound, or in need of a comparative global perspective. Social implications: – While the findings show some context-specificity for CSR in and across China, they also confirm the relevance of the originally Western CSR components to an emerging-market setting. These insights may be helpful for those interested in furthering CSR across countries, and locally as well as globally. Originality/value: – This study responds to calls for an improved understanding of the context-specificity of the originally Western CSR construct and of the extent to which it may be generalizable to non-Western settings such as China. The authors used a sample covering all regions of China and discovered two important dimensions. The results may be helpful to guide the debate on the plethora of CSR conceptualizations into a more focused direction, with clear relevance for the marketing field.